Students' Mathematical Problem Solving Ability in Terms of Gender Differences - Fathiyah Fathiyah; Ibrahim Ibrahim; Mulin Nu’man (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo,, 2021)
This study describes students' problem-solving abilities in solving exponential problems in terms of gender differences. Studies on this matter are still rarely done. This research is descriptive qualitative research. The research procedure includes: 1) the pre-field stage, namely interviews with mathematics teachers and the preparation of research instruments; 2) the research stage, namely the provision of problem-solving ability tests, gender scales, and interview guidelines; 3) The data analysis stage, namely reducing data, presenting data and making conclusions. This research was conducted at SMA N 1 Banguntapan Bantul class X MIPA 2. The instruments used were researchers, problem-solving tests, interview guidelines, and gender scales. The results of this study indicate that there are differences in gender types in the context of problem-solving. The masculine gender student solves problems and makes decisions quickly, chooses practical ways of counting, and writes short answers. Feminine gender students have good memorization in solving problems, writing down answers in detail, but hesitating in writing down answers. Students with androgynous gender in solving problems write down answers in detail and have the ability to re-explain the solving process. Meanwhile, students of the sexes cannot be differentiated in solving problems by writing inconsistent answers, using a mathematical model.